Puritan Hindus in Bolaang Mongondow: Faith, Trade and Politics - Almunawar bin Rusli; Nasruddin Yusuf (International Journal of Interreligious and Intercultural Studies, 2020)
This article look at how to become a Balinese in Bolaang Mongondow, North Sulawesi. As a trans-migrant group from the eruption of Mountain Agung Karangasem 1963, they left the Island of Gods since March 11, 1964, anchored in Makassar later arrived in Bolaang Mongondow March 26, 1964 through Inobonto port and build of Pakraman Kembang Mertha Village November 1, 1965 with permission of Dumoga indigenous peoples. The Balinese expression of faith shaping of intersubjective relation. In contrast to Geertz’s thesis about the absolute monism of Hinduism, the Balinese in Bolaang Mongondow instead used of religious pluralism perspective. They convert to Muslim and Christian without conflict. In 1970, the Bali farmers start to planting corn, soybean, cassava and rice based on family ties. They have a trade networks with Chinese ethnic descendants. In presidential election 2019, Joko Widodo-Ma’ruf Amin became the winner in Kembang Mertha (84.56%) in comparison to Prabowo-Sandi (15.44%). The loyalty of Balinese to PDIP can be survived from money politics and identity politics because of the cross-blood and ideology. Thus, Balinese migrants can be classified as one of the strongest civil society in contemporary Bolaang Mongondow.